Taxonomic notes on the genus Heliophanus C.L. Koch, 1833, with description of three additional genera (Araneae: Salticidae: Chrysillini) - Wesołowska, Wanda (Zootaxa, 2024)
Intrageneric taxonomy of genus Heliophanus C.L. Koch, 1833 is revised. Two subgenera are elevated to the generic ranks: Helafricanus Wesołowska, 1986 (type species Heliophanus patellaris Simon, 1901) and Heliocapensis Wesołowska, 1986 (type species Heliophanus peckhami Simon, 1902). Generic name Trapezocephalus Berland & Millot, 1941 is removed from synonyms of Heliophanus and reinstalled as valid genus (type species Heliophanus cassinicola Simon, 1909 = Trapezocephalus aeluriliformis Berland & Millot, 1941). Genera Helafricanus, Heliocapensis, Heliophanus s. str. and Trapezocephalus are redefined, and their updated diagnoses and compositions are given. Seventy-three new combinations are proposed from Heliophanus s. lato. Five specific names are synonymized: Heliophanus thaleri Wesołowska, 2009 with Heliophanus termitophagus Wesołowska & Haddad, 2002, Heliophanus patagiatus albolineatus Kulczyński, 1901 with Heliophanus patagiatus Thorell, 1875, Heliophanus montanus Wesołowska, 2006 with Heliophanus capicola Simon, 1901 (and transferred to Trapezocephalus), Heliophanus berlandi Lawrence, 1937 with Baryphas ahenus Simon, 1902, and Astia hariola L. Koch,1879 with Heliophanus maculatus Karsch,1878, for the latter species Astia maculata (Karsch,1878) comb. nov. is proposed. Heliophanus japonicus Kishida, 1910 is recognized as nomen dubium.